Ultra-Wideband Antennas for Wireless Communication Applications - Tale Saeidi; Idris Ismail; Wong Peng Wen; Adam R. H. Alhawari; Ahmad Mohammadi (International Journal of Antennas and Propagation)
A review paper concerning wide-band and ultra-wideband (UWB) antennas used for wireless communication purposes in terms of the materials as well as a numerical analysis is presented. These antennas which are taken into account are listed as wide-band microstrip antenna, wide-band monopole antenna over a plate, wide-slot UWB antenna, stacked patch UWB antenna, taper slot (TSA) UWB antenna, metamaterial (MTM) structure UWB antennas, elliptical printed monopole UWB antenna, and flexible wearable UWB antenna. The antennas’ performance is compared based on their size and how they can be applicable for portable communication device applications. This review paper furnishes a proper direction to select varieties of figures in terms of impedance bandwidth, gain, directivity, dimensions, time domain characteristics, and materials affecting these antenna’s characteristics.